Co-Creation and Smart Cities : Looking Beyond Technology. - Van der Graaf, Shenja (Emerald points., 2022)
Co-creation and Smart Cities: Looking Beyond Technology highlights a more robust value-based perspective on public service development and delivery, helping structure co-creation processes that foster responsible innovation and a systemic, value-based approach to sustainable urban development.